Selected Abstracts of the 17th International Workshop on Neonatology and Pediatrics, Virtual Edition; Cagliari (Italy); October 28-29, 2021 - Various Authors, --- (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2021)
SELECTED ABSTRACTS OF THE 17TH INTERNATIONAL WORKSHOP ON NEONATOLOGY AND PEDIATRICS • VIRTUAL EDITION CAGLIARI (ITALY) • OCTOBER 28TH-29TH, 2021 ABS 1. ACUTE RESPIRATORY INFECTIONS IN CHILDREN AT THE SYLVANUS OLYMPIO TEACHING HOSPITAL IN LOMÉ (TOGO) • M. Fiawoo, N.K. Douti, F. Agbeko, K.M. Guedenon, S.C. Edrih, K.E. Djadou, D.Y. Atakouma (Lomé, Togo) ABS 2. ALTERNATIVE STRATEGIES FOR THE MANAGEMENT OF PEDIATRIC ASTHMA DURING THE COVID-19 PANDEMIC: THE POTENTIAL ROLE OF TELEMEDICINE • M. Votto, M. De Filippo, A. Licari, G.L. Marseglia (Pavia, Italy) ABS 3. THE EFFECT OF MATERNAL VITAMIN D LEVELS ON HOSPITALIZED PRETERM INFANT AT BIRTH IN NICU • P.M.T. Marsubrin, A. Firmansyah, R. Rohsiswatmo, Y. Purwosunu, S. Bardosono, S.G. Malik, Z. Munasir, I.S. Timan, T. Yuniati (Jakarta and Bandung, Indonesia) ABS 4. EFFECT OF GESTATIONAL DIABETES MELLITUS ON GLUCOSE TRANSPORTERS EXPRESSION IN MILK-DERIVED MESENCHYMAL STEM CELLS • L. Moretti, A.M. Nuzzo, S. Sottemano, K. Mareschi, G. Menato, G. Maiocco, C. Peila, G.E. Moro, E. Bertino, A. Rolfo (Turin and Milan, Italy) ABS 5. PULMONARY HYPERTENSION IN BRONCHOPULMONARY DYSPLASIA: A RETROSPECTIVE STUDY OF TWENTY PRETERM • F. Mecarini, A. Atzei, D. Gariel, D. Manus, P. Neroni, F. Bardanzellu (Cagliari, Italy) ABS 6. UNEXPECTED POST-SURGICAL BLEEDING: ROLE OF STRESS ULCER PROPHYLAXIS WITH PROTON PUMP INHIBITORS (PPIs) • F. Marino, F. Rigon, S. Bellonzi, C. Lorenzetto, A. Mussari, G. Passarella, S. Rugolotto (Rovigo, Italy) ABS 7. L1 CELL ADHESION MOLECULE (L1CAM) EXPRESSION IN THE FETAL HUMAN KIDNEY DURING DEVELOPMENT • F. Cau, C. Betti, V. Aimola, R. Murru, P. Van Eyken, V. Marinelli, M.C. Botta, Y. Gibo, G. Faa, C. Gerosa, D. Fanni (Cagliari and San Gavino, Italy; Genk, Belgium; Matsumoto, Japan; Philadelphia, PA, USA) ABS 8. NEW THERAPEUTIC STRATEGIES IN PEDIATRIC ALLERGY • M. De Filippo, M. Votto, A. Licari, G.L. Marseglia (Pavia, Italy) ABS 9. BACTERIAL PATTERN OF THE SEPSIS PATIENTS ADMITTED TO THE NICU OF BUDHI ASIH REGIONAL PUBLIC HOSPITAL (JAKARTA) FROM JANUARY 2019 TO OCTOBER 2020 • M.E. Yuliana, R. Sihombing (Jakarta, Indonesia) ABS 10. CONGENITAL CYTOMEGALOVIRUS INFECTION: CAN THE DIFFERENCE BETWEEN THE VIRUS’ RELATIONSHIP WITH THE HOST’S IMMUNE SYSTEM EXPLAIN THE DIFFERENCE IN CLINICAL PHENOTYPES? • A. Spadavecchia, A. Leone, V. Dell’Oste, M. Biolatti, A. Coscia, F. Cresi, C. Peila, C. Rubino, E. Bertino (Turin, Italy) ABS 11. A PERSISTENT AND RESISTANT DUCTUS ARTERIOSUS • G. Concas, A. Atzei, F. Birocchi, F. Cioglia, F. Bardanzellu, P. Neroni (Cagliari, Italy) ABS 12. ACUTE SUPPURATIVE THYROIDITIS IN A 4-YEAR-OLD BOY: A CASE REPORT • V. Aimola, G. Cerrone, D. Fanni, C. Gerosa, R. Puxeddu, G. Faa, M.L. Lai (Cagliari, Italy) ABS 13. NEONATAL COMPLICATIONS ASSOCIATED WITH EMERGENCY CESAREAN SECTION AND INSTRUMENTAL DELIVERY • M. Fiawoo, N.K. Douti, K.M. Guedenon, F. Agbeko, M. Hemou, E. Tsolenyanu, O.E. Takassi, D.A.E. Akolly, O-B. Tchagbélé, K.E. Djadou, D.Y. Atakouma (Lomé, Togo) ABS 14. IS IT SYNDROME OF INAPPROPRIATE ANTIDIURETIC HORMONE SECRETION OR CEREBRAL/RENAL SALT WASTING SYNDROME? • F. Bardanzellu, M.A. Marcialis, R. Frassetto, A. Melis, V. Fanos (Cagliari, Italy) ABS 15. POLAND SYNDROME: A CASE REPORT • F. La Ciacera, A. Lussu, V. Pisano, M. Scarano, L. Pibiri (Cagliari, Italy) ABS 16. EXPRESSION OF BRAIN-DERIVED NEUROTROPHIC FACTOR AND NEUROTROPHINS 3/4 IN MILK-DERIVED MESENCHYMAL STEM CELL (MDMSCs) • A.M. Nuzzo, S. Sottemano, L. Moretti, K. Mareschi, G. Menato, G. Maiocco, A. Coscia, G.E. Moro, E. Bertino, A. Rolfo (Turin and Milan, Italy) ABS 17. BLASTIC PLASMACYTOID DENDRITIC CELL NEOPLASM (BPDCN) IN A 15-YEAR-OLD GIRL • G. Cerrone, L. Pilloni, V. Aimola, C. Gerosa, R. Murru, F. Cau, G. Faa, L. Atzori, D. Fanni (Cagliari and San Gavino, Italy) ABS 18. MULTIPLE FETAL CARDIAC RHABDOMYOMAS ASSOCIATED WITH TUBEROUS SCLEROSIS: A PRENATAL DIAGNOSIS • F. Mecarini, A. Atzei, P. Neroni (Cagliari, Italy) ABS 19. A USEFUL EXPERIENCE: THE NORMAN PEDIATRIC AND NEONATOLOGY MEETINGS • S. Vendemmia, M. Vendemmia, G. Parisi (Aversa, Naples and Vasto, Italy) ABS 20. PRENATAL PSYCHOLOGY AND COVID-19: A LOOK AT THE FUTURE • I. Rotolo (Italy) ABS 21. NUTRIMETABOLOMICS IN WEANING • A. Bosco, R. Pintus (Cagliari, Italy) ABS 22. THE INTERNATIONAL ALFRED NOBEL’S FRIENDS STUDY CENTER IN SANREMO AND PEDIATRICS • G. Trapani (Sanremo, Italy) ABS 23. PARENTS KNOWLEDGE AND ATTITUDES REGARDING ORAL HEALTH DURING CHILDHOOD: A CROSS-SECTIONAL STUDY IN A SAMPLE OF ITALIAN CHILDREN INPATIENTS • E. Bianco, C.A. Ghitti, S. Attuati, M. Maddalone (Monza, Italy) ABS 24. A RAPID, NOVEL HOST-IMMUNE TEST PERMITS ACCURATE DIFFERENTIATION OF BACTERIAL AND VIRAL INFECTION IN FEBRILE AMBULATORY PATIENTS: THE APOLLO STUDY • F. Curenza, A. Argentiero, G. Autore, S. Esposito on behalf of the Apollo Study Group (Parma, Italy) ABS 25. FILMARRAY® RESPIRATORY PANEL AND BRONCHIOLITIS IN POST-COVID-19 ERA • L.M. Toscano, A. Tessari, F. Marino, S. Bellonzi, F. Rigon, A. Mussari, G. Passarella, C. Lorenzetto, S. Rugolotto (Padua and Rovigo, Italy) ABS 26. MICROBIOTA PROFILES IN PRE-SCHOOL CHILDREN WITH RESPIRATORY INFECTIONS: MODIFICATIONS INDUCED BY THE ORAL BACTERIAL LYSATE OM-85 • F. Cusenza, G. Autore, S. Ballarini, A. Argentiero, L. Ruggiero, G.A. Rossi, N. Principi, S. Esposito (Parma, Perugia, Milan and Genoa, Italy) ABS 27. INTRAVENTRICULAR HEMORRHAGE AND PERIVENTRICULAR HEMORRHAGIC INFARCTION IN A FULL-TERM NEWBORN WITH HETEROZYGOUS PROTHROMBIN G20210A GENOTYPE • F. Bardanzellu, V. Masile, C. Fanni, M.C. Pintus, F. Cioglia, V. Fanos, M.A. Marcialis (Cagliari, Italy) ABS 28. ABNORMAL HIP SYNOVITIS • B.M. Trapani (Bellinzona, Switzerland) ABS 29. ANTIBIOTIC RESISTANCE OF UROPATHOGENS IN CHILDREN HOSPITALIZED FOR URINARY TRACT INFECTION IN THE EMILIA-ROMAGNA REGION, ITALY • G. Autore, F. Cusenza, S. Esposito on behalf of the UTI-Ped-ER Study Group (Parma, Italy) ABS 30. CHILDREN WITH POST-COVID-19 SYMPTOMS IN THE PEDIATRIC OUTPATIENT CLINIC: PRELIMINARY FINDINGS • G. Trapani, G. Verlato, E. Bertino, G. Maiocco, R. Vesentini, O. Al Jamal, A. Dessì, V. Fanos and the Working Group (Sanremo, Verona, Turin and Cagliari, Italy) ABS 31. CLINICAL OUTCOME ASSOCIATED WITH DISCORDANT THERAPY FOR PEDIATRIC URINARY TRACT INFECTIONS • G. Autore, F. Cusenza, S. Esposito on behalf of the UTI-Ped-ER Study Group (Parma, Italy) ABS 32. TELEMEDICINE IN PEDIATRIC AND ADULT PATIENTS WITH NEUROGENIC BLADDER DURING THE COVID-19 PANDEMIC: TO MAKE A VIRTUE OUT OF NECESSITY • G. Masnata, S. Dessì, G. Sanna, L. Corona (Cagliari, Italy) ABS 33. HYPERAMYLASEMIA FROM EXTRAPANCREATIC CAUSES – CLINICAL CASE • C. Cioffi, I. Pezone, S. Cioffi, G. Gallucci, D. Perri (Aversa and Naples, Italy) ABS 34. IMPACT OF THE PUBLICATION OF THE ITALIAN GUIDELINES ON THE MANAGEMENT OF CHILDREN HOSPITALIZED FOR BRONCHIOLITIS • F. Abbate, G. Depietri, M.E. Di Cicco, D. Peroni (Pisa, Italy) ABS 35. FROM THE WORKING GROUP OF ITALIAN HOSPITAL PEDIATRICS TO THE ITALIAN SOCIETY OF HOSPITAL PEDIATRICS (SIPO) • D. Perri (Aversa, Italy) ABS 36. POTENTIAL IMPACTS OF CLIMATE CHANGE ON POLLEN ALLERGY IN CHILDREN • M.E. Di Cicco, E. Del Tufo, S. Gracci, P. Comberiati, D. Peroni (Pisa, Italy) ABS 37. FOOD PROTEIN-INDUCED ENTEROCOLITIS SYNDROME (FPIES) MIMICKING A NEONATAL SEPSIS: A DIAGNOSTIC DILEMMA • I. Pezone, C. Cioffi, G. Gallucci, S. Cioffi, D. Perri (Aversa and Naples, Italy)